KONTRIBUSI HARGA DAN PENINGKATAN KUALITAS PELAYANAN PADA KEPUTUSAN PEMBELIAN KONSUMEN UNTUK BERBELANJA PADA ALFAMART CABANG CIBEUREUM KOTA SUKABUMI: Manajemen sumberdaya manusia - Asep Suryana, SE., M.AK (Ekonomedia, 2017)
This research was conducted at Alfamart Cibeureum Branch, Sukabumi City. The purpose of this study is to determine the effect of price and product quality improvement simultaneously on consumer purchasing decisions to shop at Alfamart Cibeureum Branch, Sukabumi City. The research method used is the Associative Descriptive method. The population in this study were consumers who shopped at Alfamart Cibereum City Branch for one month and the sample used was 94 people obtained by using non-probability sampling with judgment sampling technique. Meanwhile, to test the research instrument using validity, reliability, and hypothesis testing. used t test and ui f, then analysis of the relationship used Pearson correlation, coefficient of determination and multiple linear regression analysis. Based on the results of the analysis that has been carried out, it can be seen that the correlation test shows that the correlation value of Price on Purchase Decisions is 0.947 and includes a very strong correlation category because it is in the interval "0,800-1,000", that the correlation value of Service Quality with purchasing decisions is 0.941 and belongs to the category of very strong correlation because it is in the interval “0,800 - 1,000. Based on the analysis of the determination test of the contribution of the influence of the application of Price and Service Quality on the Purchase Decision, the calculation results obtained that the R Square value of the Purchase Decision was 0.904 or 90.4%, the remaining 9.6% was influenced by variables other than Price and Service Quality which were not examined by researchers. Furthermore, multiple linear regression analysis obtained the value of the independent variable constant. Y = 5.671 + 0.653 X + 0.293 X + . Based on the regression equation, it can be translated: that the constant value (a) has a value of 5.671 which states that if the price (X1) and service quality (X2) does not increase or equal to 0, then the value of the purchase decision (Y) is 5.671 times. .